COUNSELING FOR ANXIETY IN EXPERIENCING STRESS AND DIFFICULTIES IN LIFE FOR CHRISTIANS - Suwito , Tri Prapto; Sembiring , Milisi (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
Worry is a form of erratic anxiety, even if it happens in an exaggerated mind, it will not necessarily happen. Every human being has a sense of worry as a feeling of protection for what has not yet happened in front of him. Worries can take the form of job loss, stalled business in life, expensive education costs, a near-stalled economy, labor layoffs, children fighting parents, cheating husbands, wives leaving the house, having children with special needs, anxiety about the future, and any form of difficulty, all of which cause stress, suffering, and other difficulties in life.In this journal, the author makes research in a qualitative explanation, coming from various book sources, various journals related to psychology, counseling and it is hoped that this journal will obtain research results that can answer various problems regarding concerns experienced for Christians, so that they can respond correctly to the truth of God's Word.